Positive psychology the scientific and practical explorations of human strengths - Snyder, C. R.; Lopez, Shane J. (Sage Publiscations Ltd., 2011)
Offer comprehensive coverage of the science and application of positive psychology and present new frameworks for understanding positive emotions and human strengths. The authors bring positive psychology to life by tackling issues such as how positive psychology can help improve schooling and the workplace, as well as promote cooperative lifestyles among people. Further, the book covers Western and Eastern approaches to understanding human strengths, along with the cultural and developmental influences on positive functioning. The authors also explore various positive conditions such as happiness and well-being, along with other processes related to mindfulness, wisdom, courage, and spirituality. Features of the Second Edition: - Offers an in-depth discussion of science and applications: The book provides the most comprehensive coverage of postive psychology's science and applications. It explores various positive conditions such as empathy, altruism, gratitude, attachment and love. - Encourages active learning: The authors include over 50 case studies, grounded in the practice, research, teaching, and daily lives of the authors that reveal how positive psychological phenomenon operates in the lives of real people. Personal Mini-Experiments and Life Enchancement Strategies help readers apply knowledge of the science and practice of positive psychology in their lives. - Instructor's Resource Site is available to adopters. New to the Second Edition: - Updated with the latest research in positive psychology that covers topics such as hope, courage, altruism, and more - Provides examples and research from many different cultural groups that includes such facets as race, ethnicity, socioeconomic status, sexual orientation, gender, nation of origin and others.